Computer-aided applications of nanoscale smart materials for biomedical applications. (October 2008) - Rakesh, L; Howell, B A; Chai, M; Mueller, A; Kujawski, M; Fan, D; Ravi, S; Slominski, C
Nanotechnology has the potential to impact the treatment of many diseases that currently plague society: cancer, AIDS, dementia of various kinds and so on. Nanoscale smart materials, such as carbon nanotubes, C60, dendrimers and cyclodextrins, hold great promise for use in the development of better diagnostics, drug delivery and the alteration of biological function. Although experimentation is being used to explore the potential offered by these materials, it is by its very nature expensive in terms of time, resources and expertise. Insight with respect to the behavior of these materials in the presence of biological entities can be obtained much more rapidly by molecular dynamics simulation. Furthermore, the results of simulation may be used to guide experimentation so that it is much more productive than it might be in the absence of such information. The interactions of several nanoscale structures with biological macromolecules can already be probed effectively using molecular dynamics simulation. The results obtained should form the basis for significant new developments in the treatment of disease.